1993
DOI: 10.1111/j.1399-6576.1993.tb03727.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement by ischemia of the risk of cardiac disorders, especially fibrillation, in regional anesthesia with bupivacaine

Abstract: The impairment of intraventricular conduction by bupivacaine may result in reentrant arrhythmias including ventricular fibrillation. The concentrations responsible for serious accidents are high (5.0 to 8.0 micrograms/ml), but likely to be lowered by myocardial ischemia which gives rise to similar disorders. Therefore we did an electrophysiological study of bupivacaine's effects in an ischemic area of the myocardium. Monophasic action potential (MAP) of the ventricular myocardium was recorded in 30 anesthetize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Pacini et al [67] revealed that the effect of lidocaine on sheep Purkinje fibers is greater under simulated ischemia than that in normal conditions. Freysz et al [68] also reported that the risk of cardiac disorders in bupivacaine anesthesia was increased by ischemia. However, the detailed mechanism remains unclear for the local anesthetic cardiotoxicity altered by ischemia.…”
Section: Membrane Interaction Associated With Cardiotoxicitymentioning
confidence: 99%
“…Pacini et al [67] revealed that the effect of lidocaine on sheep Purkinje fibers is greater under simulated ischemia than that in normal conditions. Freysz et al [68] also reported that the risk of cardiac disorders in bupivacaine anesthesia was increased by ischemia. However, the detailed mechanism remains unclear for the local anesthetic cardiotoxicity altered by ischemia.…”
Section: Membrane Interaction Associated With Cardiotoxicitymentioning
confidence: 99%
“…In addition, myocardial ischemia significantly increases the risk for VF following accidental intravascular LA injection. Previous experiments in our laboratory have shown a close correlation between VF propensity and myocardial ischemia with both bupivacaine [7] and ropivacaine [8].…”
Section: Introductionmentioning
confidence: 62%
“…As example, in vivo and in vitro models using ischemic/reperfused and/or hypoxic conditions have successfully evidenced the proarrhythmic potential of several therapeutic classes of compounds such as K-ATP channel activators [115,137], Class I antiarrhythmics [138][139][140][141] or anesthetics [142,143]. Despite their recognized comprehensive and predictive value, these models remain however difficult to run routinely.…”
Section: Models For Risk Assessment Related To Heterogeneous Repolarimentioning
confidence: 99%